2021
DOI: 10.1136/heartjnl-2020-317761
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic disparities in prehospital factors and survival after out-of-hospital cardiac arrest

Abstract: ObjectiveIt remains unknown whether patient socioeconomic factors affect interventions and survival after out-of-hospital cardiac arrest (OHCA), and whether a socioeconomic effect on bystander interventions affects survival. Therefore, this study examined patient socioeconomic disparities in prehospital factors and survival.MethodsFrom the Danish Cardiac Arrest Registry, patients with OHCA ≥30 years were identified, 2001–2014, and divided into quartiles of household income (highest, high, low, lowest). Associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 20 publications
3
29
1
Order By: Relevance
“…A recent Danish study, including OHCAs of cardiac origin, revealed similar results, with a clear association between income and the chance of 30-day survival. 13 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent Danish study, including OHCAs of cardiac origin, revealed similar results, with a clear association between income and the chance of 30-day survival. 13 …”
Section: Discussionmentioning
confidence: 99%
“… 9 Previous studies carried out with individual-level data are few and have suffered from small sample sizes as well as reliance on specific subgroups of the OHCA population, such as children and adolescents, 10 patients with shockable rhythm, 11 patients admitted to hospital, 12 and cardiac arrests of cardiac origin. 13 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the latter only accounted for less than 1% of the difference in survival across the income groups. 3 Another, probably more likely, explanation for the observed difference in survival, mentioned by Møller et al, is the quality of the intervention as performed by the bystander. Similar findings were obtained when categorising patients based on their level of education.…”
Section: Successful Resuscitation Of Sudden Cardiac Death: Education Mattersmentioning
confidence: 97%
“…Similar findings were obtained when categorising patients based on their level of education. 3 The study conducted by Møller et al shows that survival following SCD depends on one's socioeconomic status, among other factors. Reducing the socioeconomic disparity in survival seen in these patients should be high on the agenda of all stakeholders.…”
Section: Successful Resuscitation Of Sudden Cardiac Death: Education Mattersmentioning
confidence: 99%